PENINGKATAN PENGETAHUAN MASYARAKAT TENTANG DAMPAK EROSI TERHADAP LINGKUNGAN DI DESA MEKARWANGI PANDEGLANG - Fathin Rahman; Syaiful Anwar; Muhammad Nuur Farid Thoha; Wuri Septi Handayani (Aptekmas Jurnal Pengabdian pada Masyarakat, 2023)
Farmers' low knowledge of soil and water conservation can cause agricultural land to be vulnerable to erosion and environmental damage. The purpose of the community service activities carried out in Mekarwangi Village, Saketi District, Pandeglang is to provide knowledge to the farming community about the types of erosion and their prevention efforts in the form of vegetation methods, technical methods, and chemical methods. Based on the results of the questionnaires that have been collected, it means that before the counseling was carried out, the participants had very little information about the types of erosion, direct and indirect impacts, and prevention methods. After the extension was carried out, it was seen that there was a very significant increase in the knowledge of the farming community regarding erosion and the understanding that so far the management of agricultural land that had been carried out was not appropriate for slope conditions, which resulted in erosion and environmental damage.